Pengembangan Media Pengenalan Produk UMKM Makanan Khas Tegal Berbasis Augmented Reality - Priyanto, Diaz Ananda; Armin, Aidil Primasetya (Jurnal Ilmu Siber dan Teknologi Digital, 2025)
Purpose: This study aimed to develop an interactive and accessible Augmented Reality (AR)-based media to introduce traditional culinary products from Tegal, which remain relatively unknown among the people in Surabaya. Methodology/approach: To carry out this study, the Multimedia Development Life Cycle (MDLC) model was utilized. The resulting system is a web-based Augmented Reality application that uses marker-based tracking to visualize 3D models of traditional foods from Tegal. The 3D visual elements were designed using the Blender application. Results/findings: The system effectively introduced new information to all respondents, especially those who were previously unfamiliar with Tegal's traditional cuisine. Usability testing showed a System Usability Scale (SUS) score of 77.08, indicating that the system was well received and suitable for use. Conlusion: The developed system is considered effective and engaging as a medium for introducing local culinary heritage to a broader audience. Limitations: The system depends on marker-based AR, which requires physical markers and may limit its flexibility. Contribution: This study contributes to cultural preservation and educational media by providing a digital platform for introducing regional culinary heritage, especially for local governments, the tourism sector, and educational institutions.